PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIA SMP NEGERI 1 LOGAS TANAH DARAT - Hartina, Dwi Putri; Hutapea, Nahor Murani; Jalinus, Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to improve and the student’s mathematics learning outcomes through implementation of Problem Based Learning (PBL) Model. This type of research is Classroom Action Research with two cycle. The research was conducted in class VIIA SMP Negeri 1 Logas Tanah Darat in the odd semester of the academic year 2018/2019. The subject of this research consist of 22 students. The research instrument consists of learning materials used include Syllabus, Lesson Plan and Student Activity Sheets and instruments for collecting data are observation sheets and test of mathematics learning outcomes. Data analysis techniques in this study are descriptive narrative analysis and descriptive statistics analysis. The percentage and frequency of students who achieved minimum completeness criteria is increased from the basic score are 8 students with percentage 36,36% to cycle I are 12 students with percentage 54,55% and from cycle I to cycle II are 19 students with percentage 86,36%.. This research concludes that the implementation of PBL model improved the student’s mathematics learning out comes at class VII6 SMP Negeri 1 Logas Tanah Darat in the odd semester of the academic year 2018/2019 in construction material.Key Words: Problem Based Learning model, Mathematics Learning Outcomes